KESANTUNAN IMPERATIF DALAM INTERAKSI ANTARMAHASISWA FAKULTAS TARBIYAH DAN ILMU KEGURUAN IAIN PONTIANAK: Kajian Pragmatik dan Etis Pendidikan Islam - Muchammad Djarot; Marsih Muhammad (IAIN Pontianak, 2019)
Imperative politeness is one of focus in character building education. This is because language politeness or in spoken language is part of main pilars in character education. Based on the research, students of teacher training and education faculty in State Islamic Institute Pontianak showed the students tend less polite in spoken. This reveals from their imperative spoken in interaction among them. Meanwhile their spoken language that they used represents their characteristics and become problematic because they are studying at teacher training and education faculty in State Islamic Institute Pontianak in which is place for graduating candidate of teachers. In methodology, this research is qualitative with pragmatic approach. In the research, method of collecting data used method of listening and capability. Object of the research is students who study at teacher training and education faculty in State Islamic Institute Pontianak.